Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1364/opn.17.4.000018
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Slow Light in Telecommunications

Abstract: Form Approved OMB No. 0704-0188Public reporting burden for the collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing the collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing this burden, to Washington Headquarters Services, Directorate f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
105
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 219 publications
(107 citation statements)
references
References 3 publications
1
105
0
1
Order By: Relevance
“…We have also experimentally demonstrated control of the cross-talk and have shown that the analytical solutions presented yield good quantitative agreement with the experiment. Effective control of cross-talk in the double-ladder system could find many potential applications in optical communication [29] and in quantum information processing as a controllable correlated photon source [30].…”
Section: Discussionmentioning
confidence: 99%
“…We have also experimentally demonstrated control of the cross-talk and have shown that the analytical solutions presented yield good quantitative agreement with the experiment. Effective control of cross-talk in the double-ladder system could find many potential applications in optical communication [29] and in quantum information processing as a controllable correlated photon source [30].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover the performance required by modern telecommunication systems and optical digital processing in terms of delay and bandwidth would require a tremendous pumping power that turns the endeavour into a lost cause [20]. It means that slow-and fast-light delay lines are likely to miss the main target application that motivated the early research efforts, which is the all-optical buffering for the development of future all-optical routers [22]. For such an application, coherent optical storage looks more like a promising approach and recent results show that even SBS can realize this storage function in optical fibres [23].…”
Section: Discussionmentioning
confidence: 99%
“…Although other technologies, such as coupled resonators 6,50 , potentially provide improved storage capabilities, the all-optical and fast delay control that characterizes the fibre-based techniques is not yet possible in such structures. This means that it is difficult for slow-and fast-light delay lines to meet the target application that motivated the early research efforts, that is, the all-optical buffering required for future all-optical routers 51 . For such an application, wavelength conversion associated with a dispersive optical line has proven to be an efficient solution, and the delaying of a full sequence of 1,000 bits at 10 Gbit s -1 has already been demonstrated [52][53][54] .…”
Section: Review Article | Focusmentioning
confidence: 99%